Implementasi Permainan Edukasi Ular Tangga Dalam Mengembangkan Kemampuan Kognitif Anak Usia 5-6 Tahun - Ria Kurniawaty (Yinyang: Jurnal Studi Islam Gender dan Anak, 2022)
Basically the study is on the background of the symptoms of children being less active, learning out, maximum deficiencies in planning and game selection in child cognitive development by teachers. Hence, the study aims (1) to know the implementation of a game of snakes in developing a child's cognitive capability (2) to know a child's cognitive development (3) to know factors that affect a child's cognitive development. The study USES a descretive qualitative approach by using methods of observation, interview and documentary collections. The stage of data analysis techniques includes data reduction, data presentation and data verification. Studies have shown that: (1) implementation of a ladder game in developing a five-year-old's cognitive abilities includes: collom and RPPH contained in the event a ladder viper instrument for developing a child's cognitive. (2) then well-controlled cognitive development is as follows: name the family members, explain their surroundings, name the direction of frequent visits, follow the rules, know things around, know large amounts and are able to sequence in Numbers, shapes and sizes. (3) factors that influence a child's cognitive development include internal factors (physiological aspects) and external factors (parental upbringing and education).